Jovens, tempo e história: leituras de um caleidoscópio - Astrogildo Fernandes Silva Júnior; Selva Guimarães (EccoS – Revista Científica)
This text has the objectives to present the results of a investigation in order to comprehend the way youth students due with time, what they think about history and history teaching. The research was conducted with youth students on the ninth year of the fundamental school from municipal and state public schools located in Minas Gerais, Brazil. This research is an educational study with ethnographic inspiration that made use of several tools: observation during classes and scholar daily life, questionnaires and oral interviews. It was possible to conclude that the investigated youth students understand present time is to be lived, the future is uncertain and the past is important to reflect about the present. The majority are interested in history and showed a positive view concerning the history teaching in their lives.